Estimasi Model Permintaan Kesehatan Rumah Tangga di Indonesia pada Masa Pandemi Covid-19 - Asyifa Azizah; Yuhka Sundaya (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Symptoms of declining households access to health services occurred during the Covid-19 pandemic. Observing BPS Indonesia (2021), there appears to be a percentage change in road treatment data, and health complaints are increasing. The morbidity data for each district and city on the selected island was converted into four categories of health status: [1] very healthy, [2] healthy, [3] moderately healthy, and [4] unhealthy. This research is deductive. The method used to estimate variables is QLDV (Qualitative Limited Dependent Variable). The results of the estimated health demand function answer the issue of efforts to increase the chances of Indonesian household health levels. The simulation results with marginal effects show predictions that the opportunity of health demand will increase by 2.71 percent under conditions of food allocation of 52.89 percent, food inflation of 6 percent, health inflation of 7 percent, immunization coverage of toddlers of 84.43 percent, average education of junior high school households, and per capita income close to 10 million per year. This study successfully displayed the significance of health commodity prices that were difficult for previous researchers to display. Abstrak. Gejala penurunan akses rumah tangga terhadap layanan kesehatan terjadi pada masa pandemi Covid-19. Mengamati BPS Indonesia (2021), tampak adanya perubahan persentase pada data berobat jalan dan keluhan kesehatan yang meningkat. Data morbiditas setiap kabupaten dan kota pada pulau terpilih, dikonversi menjadi empat kategori status kesehatan: [1] sangat sehat, [2] sehat, [3] cukup sehat, dan [4] tidak sehat. Penelitian ini bersifat deduktif. Metode yang digunakan untuk mengestimasi variabel adalah QLDV (Qualitative Limited Dependent Variable). Hasil estimasi fungsi permintaan kesehatan menjawab isu tentang upaya memperbesar peluang tingkat kesehatan rumah tangga Indonesia. Hasil simulasi dengan efek marjinal menampilkan prediksi bahwa peluang permintaan kesehatan akan bertambah 2.71 persen, dalam kondisi alokasi makanan 52.89 persen, inflasi makanan 6 persen, inflasi kesehatan 7 persen, cakupan imunisasi balita 84.43 persen, ioi8oipendidikan rata-rata rumah tangga SMP, dan pendapatan per kapita mendekati 10 juta per tahun. Penelitian ini berhasil menampilkan signifikansi harga komoditas kesehatan yang sulit ditampilkan para peneliti sebelumnya.